2013
DOI: 10.17221/270/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Varietal differentiation of white wines on the basis of phenolic compounds profile

Abstract: The authenticity of grapevine varieties is a very important topic in the Czech Republic, where varietal wines is very important for wine drinkers. The wines from 7 grapevine varieties were investigated. Sixteen phenolic compounds belonging among hydroxybenzoic and hydroxycinnamic acids, stilbenes, and flavan-3-ols were analysed by HPLC method. The aim of this study was to find markers of varietal origin of wines among the phenolic compounds studied. The analytical parameters obtained were evaluated for this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…This classification indicates that the selected nine polyphenolic compounds in addition to the AA and TP indices as discriminating variables may be adequate to classify the wines by grape variety in the five groups considered. These results are consistent with the thesis that the differences related to genetic (varietal) and environmental influences are more deeply associated with the major polyphenols, [22] with mainly wine flavanols PB1 and PB2, and caftaric acid, showing the largest influence to differentiate wines by both the geographic origin and variety; similar results regarding the varietal discrimination of white wines were obtained, [23] although in this case the phenolic profile was not effective for differentiating the samples by their geographical origin.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This classification indicates that the selected nine polyphenolic compounds in addition to the AA and TP indices as discriminating variables may be adequate to classify the wines by grape variety in the five groups considered. These results are consistent with the thesis that the differences related to genetic (varietal) and environmental influences are more deeply associated with the major polyphenols, [22] with mainly wine flavanols PB1 and PB2, and caftaric acid, showing the largest influence to differentiate wines by both the geographic origin and variety; similar results regarding the varietal discrimination of white wines were obtained, [23] although in this case the phenolic profile was not effective for differentiating the samples by their geographical origin.…”
supporting
confidence: 89%
“…of catechin, epicatechin, PB1, and PB2, although found concentrations are lower than those reported for these wines in other countries. [23][24][25][26][27] However, caftaric and caffeic acids are at similar concentrations than those previously reported in Chardonnays. [23] LDA was applied to the foreign varieties wines.…”
Section: Polyphenolic Composition Of Galician White Winesmentioning
confidence: 81%
“…For the hydroxybenzoic acids displayed in Figure B, gallic acid was the major hydroxybenzoic acid detected in all 3 regions, agreeing with Tang and others () and Ma and others () reports. However, Lampíř () previously reported that protocatechuic acid was the major hydroxybenzoic acid. This disagreement might result from the different wine regions.…”
Section: Resultsmentioning
confidence: 98%
“…Significant differences were observed among the regions or varieties. In previous studies, cluster analyses (Li and others ; Ma and others ), principal component analyses (Rodríguez and others ; Elisabeta and others ), linear discriminant analyses (Tang and others ), canonical discriminant analyses (Lampíř ; Pavloušek and Kumšta ; Tang and others ), canonical correlations (Romina and others ), and other related methods are currently used for the discrimination, classification, modeling, and correlation of the wine geographic origin and grape varieties. Based on these differences and a preliminary analysis, we selected a canonical discriminant analysis for this study to try to differentiate between the geographical origins of the wine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation